Consequences of Asset Shortages in Emerging Markets - Imam, Patrick (IMF Working Papers; Working Paper ;, 2012)
We assess econometrically the impact of asset shortages on economic growth, asset bubbles, the probability of a crisis, and the current account for a group of 41 Emerging markets for 1995-2008. The econometric estimations confirm that asset shortages pose a serious danger to EMs in terms of reducing economic growth, raising the probability of a crisis, and leading to asset price bubbles. Moreover, asset shortages can also explain the current account positions of EMs. The findings suggest that the consequences of asset shortages for macroeconomic stability are significant, and must be tackled urgently. We conclude with policy implications.